Silent uterine perforation and omental embedding of a Mirena® intrauterine device in a postpartum patient with undiagnosed uterine anomaly: a case report - Van Der Hock, Sarah; Seth, Ishith; Dhupar, Nita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Levonorgestrel-releasing intrauterine systems (LNG-IUS) are commonly used for long-acting reversible contraception. While generally safe and effective, they carry a rare but serious risk of uterine perforation, particularly in the presence of risk factors like recent childbirth, breastfeeding or congenital uterine anomalies. We present the case of a 35-year-old, gravida 5 para 3, female who presented with chronic abdominal pain and missing intrauterine device threads ten months after postpartum Mirena® insertion. Transvaginal ultrasound failed to visualise the device. A pelvic X-ray and computed tomography (CT) scan confirmed extrauterine migration, with the intrauterine device (IUD) embedded in the omentum. Laparoscopy revealed a scar on the posterior uterine wall suggestive of silent uterine perforation, and hysteroscopy demonstrated a subseptate uterus. The device was successfully removed laparoscopically. This case emphasises the importance of anatomical screening prior to IUD insertion, the need for post-insertion imaging, and timely investigation of symptoms. It highlights how silent uterine perforation and subsequent delayed diagnosis of IUD-related complications can be avoided through adherence to established clinical guidelines, such as those provided by the Royal College of Obstetricians and Gynaecologists (RCOG) and Faculty of Sexual and Reproductive Healthcare (FSRH) recommendations.